Physiological Character of Cocoa Clones that Cultivated under Three Species of Shade Trees - Oscar Regazzoni; Yogi Sugito; Agus Suryanto; Adi Prawoto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
This experiment aims to know the solar energy efficiency of four clones of cocoa that cultivated under three different shading plants. This experiment has been done from September until December 2013 located at Kaliwining Experiment Farm with characteristic 45 m above sea level, soil type is low humic gley, soil texture is silty clay loam, and climate classification type D based on Scmidht and Fergusson classification. This experiment used nested design as experimental design with species of shading plant as main plot which are teak (Tectona grandis L.), krete (Cassia surattensis (Burm.) F.), lamtoro (Leucaena leucocephala L.) and cocoa clones as sub plot which are Sulawesi 1, Sulawesi 2, KKM 22, and KW 165. The observation of physiological character consists of the level of leaf chlorophyll, the level of leaf nitrogen, spesific leaf area, leaf area index, the amount of stomata, and stomatal density. The experimental result showed that there is differences (heterogenity) between shading location based on homogenity test by Bartlett method. The interaction effect between plant spesies and cocoa clones are affect the leaf area index and stomatal density, whereas the level of leaf chlorophyll, the level of leaf nitrogen, and spesific leaf area was affected by the kind of plant spesies. Keywords : Physiological character, cocoa Ccones, shading trees, nested design, Bartlett method